Product diversification of jackfruit - AKHILA B. G; Shareena K. P; Er. Rajesh G. K (Guide) (Tavanur 2009 Department of Post Harvest Technology & Agricultural Processing)
Jackfruit was considered as heavenly fruit by ancient people of Kerala.
Product diversification of jackfruit